Gender Inequality in Multidimensional Welfare Deprivation in West Africa : The Case of Burkina Faso and Togo - Agbodji, Akoété Ega; Batana, Yélé Maweki; Ouedraogo, Dénis (World Bank, Washington, DC, 2013)
The importance of gender equality is reflected not only in the Millennium Development Goals, but also in the World Bank's Gender Action Plan launched in 2007 as well as in other treaties and actions undertaken at regional and international levels. Unlike other work on gender and poverty, which is mostly based on monetary measurement, the present study makes use of a counting approach to examine gender issues in Burkina Faso and Togo using household surveys. Focusing on six dimensions (housing, basic utilities, assets, education, employment, and access to credit) largely recognized as Millennium Development Goal targets, the main findings of the study indicate that overall individuals are the most deprived in education in Burkina Faso, while the reverse situation is true in Togo. Gender inequality is observed in all dimensions since women always seem to be more deprived than men. The situation is also marked by regional disparities. Moreover, the assessment of dimensional contributions shows different patterns for each country. While employment proves to be the main contributor of gender inequality in Burkina Faso, three dimensions (assets, access to credit, and employment) account together for most of the total contribution to gender inequality in Togo. There is also a positive correlation between multidimensional deprivation and women's age in Burkina Faso, whereas both measures seem to be uncorrelated in Togo.